A model for dynamic alliance networks. (4th May 2020) - Ali, Abdussalam; Hawryszkiewycz, Igo
Abstract : Business networks are now becoming increasingly important in the business environment. Their nature is also changing because of the increasing complexity of the business environment, which now not only calls for exchange of resources but also to create new knowledge to address emerging issues and improve the products and services of network partners. Developing new knowledge often calls for changes in network membership, and in changes the way the network operates. In many cases, specialized knowledge is transient in nature; it is often required quickly and hence needs to be quickly developed. The result is that business networks are becoming increasingly dynamic in nature as they require to continually adapt to changes in the business environment often by change of membership and what members do. There are, however, many ways to organize a business network. This paper describes a study of a large number of business network arrangements found in practice. The paper then identifies common characteristics of networks and develops a model that can be used to classify business networks in terms of these characteristics. The model defines levels that distinguish between organizational and operational levels now increasingly used in creative organizations. The levels are defined in terms of common characteristics that include governance, collaboration, knowledge, and privacy. The paper then describes ways to model networks in terms of the common characteristics and verified implementation of the model. Businesses wishing to set up a business network can describe it in these characteristics and convert it to a computer support system. It shows how to organize networks where strategic planning, team management, information and knowledge systems, and CoDesign can be combined in flexible ways to meet emerging needs.